Response of soil enzyme activity and soil bacterial community to PCB dissipation across different soils. (November 2021) - Du, Junjie; Hou, Fen; Zhou, Qixing
Abstract: Soils are a repository for polychlorinated biphenyls (PCBs). A pot incubation experiment was performed with four soils (black soil, paddy soil, oasis soil, and fluvo-aquic soil) treated with Aroclor 1242 to achieve PCB concentrations of 5 mg kg −1 . The soil enzyme activities of protease, phosphatase, catalase, dehydrogenase, and laccase were determined by spectrophotometry. The soil bacterial communities were investigated using Illumina sequencing analysis. The results showed that the characteristics of the test soils varied among the soil types. The fluvo-aquic soil had the greatest PCB dissipation rate (86.41%), followed by the oasis (79.31%), paddy (56.09%), and black (50.65%) soils. The soil pH, cation exchange capacity, soil organic matter content, and particle diameter played significant roles in PCB dissipation from soils. The soil type had a greater influence than PCB contamination on the soil enzyme activities and bacterial communities (alpha diversity, community structure, and composition). Among the four soils, the bacterial communities of the fluvo-aquic soil were the most susceptible to PCB contamination. However, the bacterial communities of the black soil were not changed by PCB contamination. Graphical abstract: Image 1 Highlights: Soil pH, CEC, SOM and particle diameter affect PCB dissipation strongly. Soil types affect soil enzyme activity and more than PCB contamination. Soil types affect soil bacterial community more than PCB contamination. The bacterial communities of fluvo-aquic soil were susceptible to PCB contamination. The bacterial communities of black soil remained stable after PCB contamination.